Development of an antifungal film by polyethylene surface modification with natamycin - Grafia, Ana Luisa (2018)
An antifungal low-cost film for cheese packaging was developed using a tailor-made coating process by direct natamycin (Nat) spraying onto heat softened polyethylene film surface. Two spraying systems Nat/ethanol solution and Nat/n-heptane suspension with the same Nat concentration were explored. To select the adequate system, differences in coating efficiency regarding shape, size, dispersion and distribution of particles, as well as polyethylene film/Nat adhesion and antifungal activity of both modified films were assessed and compared. Besides, the suitability of final product related to its use as food flexible packaging was considered. The results indicate that Nat coating is achieved either by direct particle incorporation (from a suspension) or by its in-situ formation (from a solution). Both kind of Nat coated films have shown antifungal effectiveness against A. niger even after severe extraction treatments. The proposed versatile process is feasible to be industrially scaled and allows to obtain an antifungal film suitable for cheese packaging that can be intensively handled without losing their activity.